2022
DOI: 10.1155/2022/8046496
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community Participation in Planning and Executing Malaria Interventions: Experience from Implementation of Biolarviciding for Malaria Vector Control in Southern Tanzania

Abstract: Background. Malaria remains a disease of great public health importance in 85 countries globally. Developing countries face resource constraints in implementing public health interventions aiming at controlling malaria. Promoting community participation may contribute to rational and effective use of resources and therefore facilitating achievement of intervention goals in a cost-effective manner while fostering sustainability. However, this can be possible if the community is engaged at all stages of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Thirty studies also reported changes in knowledge of malaria prevention (n=30),14 30 33 36 38–40 43 44 49 50 57–59 62 64 68 73 74 76 80 84–88 90 91 97 98 including improvement in the overall knowledge for malaria transmission, signs and symptoms, prevention using LLINs,14 38–40 44 57–59 64 73 74 85 86 88 90 91 97 98 vector control,36 43 98 and MDA 14 90. Behaviour outcomes were reported by 23 studies35 36 39 40 43–46 48 51 52 58 60 61 71 75 77 85 86 92 96 98 of which most of the studies reported improved use of LLIN (n=12)33 36 40 44 45 48 58 60 75 77 85 96 followed by treatment-seeking behaviour for malaria (n=7) 44 45 51 52 58 61 86. Although improved participation in vector control activities were reported by some studies (n=3),43 44 46 low participation was observed by one study71 despite the community having a good vector knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty studies also reported changes in knowledge of malaria prevention (n=30),14 30 33 36 38–40 43 44 49 50 57–59 62 64 68 73 74 76 80 84–88 90 91 97 98 including improvement in the overall knowledge for malaria transmission, signs and symptoms, prevention using LLINs,14 38–40 44 57–59 64 73 74 85 86 88 90 91 97 98 vector control,36 43 98 and MDA 14 90. Behaviour outcomes were reported by 23 studies35 36 39 40 43–46 48 51 52 58 60 61 71 75 77 85 86 92 96 98 of which most of the studies reported improved use of LLIN (n=12)33 36 40 44 45 48 58 60 75 77 85 96 followed by treatment-seeking behaviour for malaria (n=7) 44 45 51 52 58 61 86. Although improved participation in vector control activities were reported by some studies (n=3),43 44 46 low participation was observed by one study71 despite the community having a good vector knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Using the World Bank classification of countries by regions (online supplemental figure 2a), the majority of the studies were conducted in SSA (n=46)17 30–72 (table 1) followed by EAP (n=24)14 73–95 (table 2), SEA (n=3),96–98 and LAC (n=2)91 99 regions (table 3). More than half of the SSA studies were conducted in three countries: Uganda (n=12);34 51–56 58–61 63 Kenya (n=8);30 32 41 46 62 64 66 69 and Malawi (n=5) 17 49 50 68 70 72.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations